Nonperturbative treatment of single ionization of H2 by fast highly-charged-ion impact - Sælen, L.; Birkeland, T.; Sisourat, Nicolas; Dubois, A.; Hansen, J. P. (Physical review. A, Atomic, molecular, and optical physics, 2010)
We present a detailed analysis of the interference effects observed for ionization in collisions of fast highly charged projectiles with molecular hydrogen. We propose a nonperturbative semiclassical approach to describe the process under consideration by solving the time-dependent Schrödinger equation fully numerically on a 3D spatial grid. We present results for Kr34+-H2 collisions at 63 MeV/u impact energy and discuss different structures observed experimentally in doubly differential cross sections. The presence of Young-type minima and the absence of high-frequency oscillations are especially addressed. We also report unexpected interference patterns which can be observed for fixed-in-space molecular targets.